Preparation of highly luminescent BaSO4 protected CdTe quantum dots as conversion materials for excellent color-rendering white LEDs. Issue 12 (10th February 2015) - Chang, Yajing; Yao, Xudong; Zhang, Zhongping; Jiang, Danlu; Yu, Yalan; Mi, Longfei; Wang, Hui; Li, Guopeng; Yu, Dabin; Jiang, Yang
Abstract : For the first time, colloidal CdTe quantum dots are incorporated into an inorganic matrix, BaSO4, through a co-precipitation method. Abstract : The incorporation of colloidal CdTe quantum dots into an inorganic matrix, BaSO4, through a handy and rapid co-precipitation method is demonstrated for the first time. Owing to the protection of the BaSO4 matrix, the resulting composites show stronger luminescence, longer fluorescent lifetime, and higher photo- and thermal stability as well as being more anti-acid compared to the parental CdTe QDs. Moreover, the composites hold several advantages for industrial applications. White light-emitting diodes (WLEDs) utilizing the composites as a red color conversion layer are fabricated, and produce bright white light with high color-rendering properties including a CIE coordinate of (0.34, 0.33), an R a of 88, and a T c of 5112 K at 20 mA, suggesting their great potential application in a solid-state lighting system with high color-rendering properties.